Some New Heritage Discoveries in The Central Highlands, Vietnam - Phuc, La The; Su, Nguyen Khac; Tuat, Luong Thi; Duc, Vu Tien; Thom, Bui Van; Minh, Nguyen Trung (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 1, 2020)
A series of new heritage discoveries were found during several field-trips from November 2018 to May 2019 in whole area of The Central Highlands with supporting from the project, coded TN17/T06. The most remarkable discoveries are two archaeological sites: The first one is located on Ho Tre crater in Krong Ana district, Dak Lak province and the second one – along the Ba river ancient valley, in Phu Thien district, Gia Lai province. On Ho Tre crater, we collected many types of archaeological artifacts, including stone hand-axes in oval and short shapes, stone cores, flakes, grind-stones, making-fire stones (?), and several broken fragments pieces of pottery, which featured for the shape and technique types in the Neolithic Age. In archaeological sites in Phu Thien district, a series of stone tools, including uni-facial and bi-facial tools, rough-cutting tools such as side-chopper, end-chopper scrapers, spearhead tools, flake tools, etc., characterized as the shape and technique types in duration the Paleolithic Age were found. These findings play an important role in science to clarify development process of human history since pre-history up to now in Vietnam and in the region as well. Moreover, it is more significant to possibly establish a conservation strategy and to locally develop tourism. Keywords: Archaeological site, stone tool, Paleolithic, Neolithic, The Central Highlands.